2021
DOI: 10.1016/j.jad.2021.08.091
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the COVID-19 pandemic for people with bipolar disorders: A scoping review

Abstract: Introduction The COVID-19 (coronavirus disease 2019)-related pandemic represents a global source of societal and health burden. Yet, the impact of the pandemic on people with severe mental illness, including bipolar disorder (BD), remains unclear, warranting scoping review on the matter. Methods The MEDLINE and EMBASE databases were systematically searched from inception up to April 24, 2021, adopting broad inclusion criteria to assess a variety of clinical and public h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 49 publications
(111 reference statements)
1
40
1
Order By: Relevance
“…Previous research has shown the importance of active solicitation of information [68] and EMRs are now being used to help evaluate the effectiveness [69] and potential side effects [70,71] of COVID-19 vaccines. Similarly, EMR-based data has been utilized previously in studies looking at the effects of the COVID-19 pandemic as a stressor on people with bipolar disorder [72], the safety of the COVID-19 vaccine in pregnant women [73], the effect of COVID-19 on pregnancy outcomes [74], the effects of clinical characteristics on outcomes of COVID-19 patients [75][76][77], the factors that influence pharmacotherapy for tobacco dependence in the VA system [78], the effect of mental health disorders on COVID-19 mortality [79], COVID-19 vaccine adverse effects [68], and the effects of the COVID-19 pandemic on body mass index in children [80]. Thus, the present study builds upon a growing body of research examining similar effects of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown the importance of active solicitation of information [68] and EMRs are now being used to help evaluate the effectiveness [69] and potential side effects [70,71] of COVID-19 vaccines. Similarly, EMR-based data has been utilized previously in studies looking at the effects of the COVID-19 pandemic as a stressor on people with bipolar disorder [72], the safety of the COVID-19 vaccine in pregnant women [73], the effect of COVID-19 on pregnancy outcomes [74], the effects of clinical characteristics on outcomes of COVID-19 patients [75][76][77], the factors that influence pharmacotherapy for tobacco dependence in the VA system [78], the effect of mental health disorders on COVID-19 mortality [79], COVID-19 vaccine adverse effects [68], and the effects of the COVID-19 pandemic on body mass index in children [80]. Thus, the present study builds upon a growing body of research examining similar effects of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, since our sample was retrieved from a clinic specialized in OCD, other severe mental illnesses that were likely to be impacted by the pandemic [e.g. bipolar disorder ( Fornaro et al, 2021 )] were rare. Accordingly, no significant differences regarding changes in psychological distress were found between patients with OSI and OSW.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has taken an outsized toll on the physical and mental health of individuals with SCZ, BP-I, and other severe mental illnesses [ 9 , 13 , 22 ]. A multidisciplinary panel hosted a roundtable discussion to review the literature and discuss personal experiences on the impact of the COVID-19 pandemic on the mental healthcare landscape, clinical practice, and long-term management of individuals with SCZ or BP-I.…”
Section: Discussionmentioning
confidence: 99%
“…People with SCZ, BP-I, or other severe mental illnesses have been disproportionally affected by the COVID-19 pandemic [ 10 13 ]. Illness characteristics (e.g., psychosis and cognitive dysfunction) and sociodemographic characteristics (e.g., living in group housing, being homeless) may impact pandemic-related social distancing measures in individuals with SCZ or BP-I, thus increasing infection risk [ 10 ].…”
Section: Introductionmentioning
confidence: 99%